Pedagogical Competency Development Program for Special Supervising Teachers for Slow Learner Children at SMPN 6 Jakarta - Susanti, Ayu; Aprilia, Imas Diana; Homdijah, Oom sitti (Proceeding of International Conference on Special Education in South East Asia Region, 2024)
The main philosophical foundation in implementing inclusive education in Indonesia is the Pancasila philosophy which has the motto "Unity in Diversity" which is a symbol and symbol of recognition that Indonesia is a multi-cultural, multi-ethnic and multi-language country, customs, religions and beliefs as a wealth that must be guarded, maintained and developed within the framework of the Republic of Indonesia. For this reason, abnormalities (disabilities) and giftedness are just a form of diversity, just like differences in ethnicity, race, language, culture or religion. Education should not need to differentiate between children in learning in the classroom. This is the case at SMPN 6 Jakarta as one of known to be around 12 students, the majority of whom are slow learners. Meanwhile, the condition of the teachers at SMPN 6 is also considered to have low pedagogical competence in dealing with children with slow learner needs, all of whom are general teachers. However, these limitations create problems during the learning process at school, especially in individual learning. The research results show that: (a) the pedagogical competence of special supervising teachers at SMPN 6 Jakarta is still lacking in understanding pedagogical competence; (b) the obstacle experienced by teachers is the unavailability of training programs that support teachers' understanding and mastery of students with special needs; (c) formulation of a training program to improve the pedagogical competence of special supervising teachers at SMPN 6 Jakarta for children with special needs in the form of a training program; and (d) the results of the implementation test of the pedagogical competency training program for special supervising teachers at SMPN 6 Jakarta showed that it had a significant positive impact.